Saddle point excitonic resonances in BiI3 layered single crystals - Kudryavtsev, O.O.; Lisitsa, M.P.; Motsnyi, F.V.; Virko, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Excitonic resonances near the critical saddle point of M₁ sort by van Hove have been revealed for the first time in the BiI₃ layered semiconductor. Their main parameters are estimated.